THE EFFECT OF FINANCIAL LITERACY AND FINANCIAL INCLUSION ON THE PERFORMANCE OF MSMES IN BANGKALAN DISTRICT - Nurlianti, Nurlianti; Qhodriyah, Lailiyatul (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
Micro, Small and Medium Enterprises (MSMEs) have an important role in national economic growth. MSME actors who understand financial literacy and have access to financial services will encourage their business performance. This study aims to determine the effect of financial literacy and financial inclusion on the performance of MSMEs in Bangkalan Regency. This study uses primary and secondary data. Primary data was obtained by distributing questionnaires. The analytical model used in this study is multiple linear regression analysis. The results showed that the financial literacy variable had no effect on the performance of MSMEs in Bangkalan Regency due to the impact of the Covid 19 pandemic which weakened the performance of MSMEs. The financial inclusion variable has a significant positive effect on the performance of MSMEs in Bangkalan Regency. Based on the results of the F test, it shows that the variables of financial literacy and financial inclusion together affect the performance of MSMEs in Bangkalan Regency with an r-square value of 60.3%